Puncturing notions of precarity through critical educational research on young lives in Australia: towards a critical ethnography of youth. Issue 2 (3rd May 2016) - Smyth, John
Abstract : This papers deals in a polemical fashion with what is arguably one of the most contentious issues in education – the disengagement of increasing numbers of young people from schooling. It makes the argument that what is occurring is that global forces are conspiring to position young people as a form of 'social waste' and that allowing them to be unproblematically portrayed as constituting a precariat is an over-simplification if not a misrepresentation. In making the case for a different approach, conceived in terms of a critical ethnography of student disengagement, the paper invokes a political economy approach in which learning is seen as a political act engaged in by young people. The paper concludes with a series of propositions intended to provide a different and more critically ethnographic inflection on what is occurring.